Finite element simulation of reinforced concrete deep beam with opening strengthened with FRP laminates - AbdulWahab, Osama AbdulRazak (2013)
Deep beams are typically used in tall buildings, transfer floors and offshore structures and have a lot of advantages which make their use the most feasible option in many situations. The building codes do not give any explicit guidance to designing this type of structure with opening. furthermore the theoretical model for concrete deep beam strength in shear compose FRP is very limited in the literature .A series of experimental tests from previous literature were carried out to investigate the behavior and performance of reinforced concrete deep beams with opening and concrete beams strengthened in shear with composite material such as steel fiber reinforced (SFR), aramid fiber reinforced polymer (AFRP), glass fiber reinforced polymer (GFRP) and carbon fiber reinforced polymer (CFRP) and others. This current study aims as developing a 3D finite element model of deep beam with opening and deep beam with opening strengthened in shear externally with CFRP sheets and analyzing them using explicit method in ANSYS. It will be used for modeling shear strength and comparison between them for load - deflection curve. The failure load and deformation that acquired from the 3D finite element model will be verified against published experimental data. That comparison between the numerical and the experimental results asserted that good correlation for the load and deflection curves was recorded, ANSYS can predict the crack patterns which it have good agreement with those observed in experimental work. Moreover numerical simulation results were obtained stress and strain in all specimen and that cannot be easily obtained in experimental tests